Relationship between Smoking and Quality Of Life on Patient’s with Chronic Obstructive Pulmonary Disease In Dr.Reksodiwiryo Padang Hospital - Dita Hasni; Jely Safitri; Nadia Purnama Dewi; Nilas Warlem (Universitas Muhammadiyah Surabaya, 2020)
Abstract Chronic obstructive pulmonary disease (COPD) is a lung disease with the limitation of the airway, which is not completely reversible and is progressive. One of the risk factors of this disease is exposure to cigarette smoke for a long time. The purpose of this research is to know the relationship of smoking with the quality of life of chronic obstructive pulmonary disease patients at Dr. Reksodiwiryo Padang Hospital. This cross-sectional research has been implemented in February-May 2019 and involving 35 research subjects that meet inclusion and exclusion criteria. In this study, data was obtained that 97.1% of male gender research subjects, aged 60-69 years, 37.1%, 45.7% had moderate smoking status, poor quality of life 54.3% and there was a relationship with quality of life in Dr. Reksodiwiryo Padang Hospital (P-value < 0.05). In this research can be concluded that there is a smoking relationship with the quality of life patients of chronic abortive pulmonary disease patients in Dr. Reksodiwiryo Hospital, Padang.Keywords: Smoking Status, quality of life, COPD.